Differential diagnosis of identical twins with clinical suspicion of limb-girdle muscular dystrophy - Visconti, Triana (2022)
Muscular Dystrophies (MD) are a heterogeneous group of genetic diseases that cause progressive degeneration and weakness of skeletal muscle. They are caused by molecular alterations in genes that encode structural proteins or those necessary for the stability and proper functioning of muscle fibers. Among them is Limb-girdle Muscular Dystrophy (LGMD). This work describes the case of two 7-year-old identical twins who presented muscular weakness, amyotrophy, Gowers sign +, CK of 242IU/L and a clinical suspicion of LGMD. The aim was to identify the genetic alteration associated with the clinical picture of the patients. The diagnostic algorithm was based on a whole exome sequencing (WES) study, gene variant filtering associated with LGMD, Sanger sequencing, and intrafamilial segregation of the candidate variant. From the algorithm used, the variant NM_001848.2:c.868G>A was found in COL6A1, in heterozygosis. It is a missense variant that generates the change of glycine for arginine (NP:001839.2:p.Gly290Arg). This substitution is not reported in gnomAD, but it is reported in the “Leiden Open Variation Database” associated with patients with LGMD and classified as pathogenic. Variants in COL6A1 are associated with LGMD with autosomal dominant and recessive inheritance (Ullrich congenital muscular dystrophy, OMIM:158810 and Bethlem myopathy, OMIM:254090). To corroborate the inheritance mode, an intra-familial segregation study was carried out. Therefore, it was possible to determine that the twins were the only carriers of the variant under study. To conclude, the molecular alteration associated with the patient’s clinical picture was identified, resulting in a de novo variant concordant with an autosomal dominant mode of inheritance. Finally, this work highlights the effectiveness of the diagnostic algorithm used for the detection of disease-associated variants.